2018
DOI: 10.1007/s00431-018-3202-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between different criteria for metabolic syndrome in schoolchildren from southern Brazil

Abstract: The low prevalence of MetS and the low agreement among the existing criteria suggest the elaboration of new criteria for the diagnosis of MetS in the child and adolescent population. What is Known: • There are different criteria for the diagnosis of the metabolic syndrome (MetS), without a consensus of which is the best to be used in the infant-juvenile population. What is New: • Low prevalence of MetS identified among schoolchildren and the low agreement among the existing criteria suggest the elaboration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
2
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 48 publications
1
18
2
5
Order By: Relevance
“…Why there is a need to have a simplified mathematical model in clinical practice? As highlighted above multiple criteria are there which are overlapping with slightly different cut-offs and parameters which create confusion in routine clinical practice, which may not be providing a unified diagnostic system for patients [6]. Underlying insulin resistance by using insulin-based models HOMAIR is also difficult to measure both due to cost and clinical difficulties in routine practice which makes some of the metabolic syndrome ambiguous in terms of correlation with established metabolic syndrome criteria [7].…”
Section: Insulin Resistancementioning
confidence: 99%
“…Why there is a need to have a simplified mathematical model in clinical practice? As highlighted above multiple criteria are there which are overlapping with slightly different cut-offs and parameters which create confusion in routine clinical practice, which may not be providing a unified diagnostic system for patients [6]. Underlying insulin resistance by using insulin-based models HOMAIR is also difficult to measure both due to cost and clinical difficulties in routine practice which makes some of the metabolic syndrome ambiguous in terms of correlation with established metabolic syndrome criteria [7].…”
Section: Insulin Resistancementioning
confidence: 99%
“…In this study, the prevalence of MetS as measured using the modi ed NCEP ATP III and IDF criteria was 2.3% and 1.2% respectively, and increase to 4.3% by using this study's criteria. Low prevalence of MetS was also found among adolescents(mainly in urban area) in southern Brazil(1.9% to 5.0% by using different criteria) and in many studies(1.6% to 6.3% by using the IDF criteria) [27].…”
Section: Discussionmentioning
confidence: 73%
“…Second, there are many version of criteria published for metabolic syndrome in adolescents. However, Reuter et al found low agreement between different criteria, and emphasized the importance to create speci c cutoff points of MetS components for adolescents in their region [27]. In this study, despite using current main criteria (modi ed NCEP ATP III, IDF), we establish new criteria for urban adolescents in Taipei City in Taiwan for comparison.…”
Section: Future Aspect Of Establishing Suitable Criteria Of Mets For mentioning
confidence: 92%
See 1 more Smart Citation
“…Both studies used IDF parameters [7]. Reuter et al (2018) [33] also obtained a low prevalence of MS in adolescents from Rio Grande do Sul State, by the criteria of Cook et al [34] (1.9%) and IDF (2.1%). In Piauí, studies with adolescents from private schools demonstrated MS prevalence values close to those of this research, making up more than 3% of the sample, also considering the criteria of Cook et al [34] and IDF [35].…”
Section: Discussionmentioning
confidence: 98%